Dietary inosine monophosphate improved liver health and flesh quality of gibel carp (Carassius auratus gibelio) via activating AMPK signalling pathway and enhancing the contents of muscle fat and flavour substance - Cai, Wanjie; Liu, Haokun; Fu, Lele; Han, Dong; Zhu, Xiaoming; Jin, Junyan; Yang, Yunxia; Xie, Shouqi (Frontiers in Marine Science, 2022)
Inosine monophosphate (IMP) improves the flesh quality of livestock and poultry, but studies about its effect on fishes are limited. The aim of the present study was to investigate the effect of exogenous IMP on the liver health and flesh quality of gibel carp (Carassius auratus gibelio). The results showed that IMP supplementation alleviated hepatic lipid deposition by increasing the AMP/ATP ratio and activating the AMPK signaling pathway then decreased inflammatory cytokine expression levels. Additionally, IMP increased the intramuscular fat content. Metabolomic analysis of meat revealed that the IMP, adenosine monophosphate (AMP), guanosine, inosine and purine metabolism pathways were involved in the improvements in fish meat quality, composition and taste that resulted from IMP supplementation. Our study provides a relatively comprehensive assessment of the effect of exogenous IMP on the liver metabolism and flesh quality of farmed fish. The results provide an effective food supplementation strategy for cultured fish.